Addition of acacia gum to a FOS/inulin blend improves its fermentation profile in the Simulator of the Human Intestinal Microbial Ecosystem (SHIME®). (June 2015) - Marzorati, Massimo; Qin, Bingcai; Hildebrand, Falk; Klosterbuer, Abby; Roughead, Zamzam; Roessle, Claudia; Rochat, Florence; Raes, Jeroen; Possemiers, Sam
Highlights: Impact of the partial substitution of FOS and inulin by acacia gum in a fibre blend. Addition of acacia gum led to a gradual fermentation all along the colon. Repeated administrations of the blend are needed to modulate the gut microbiota. In vitro simulators are useful tools to explain the mechanism of action of fibres. Abstract: The Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) was used to assess the impact of the partial substitution of fructooligosaccharides (FOS) and inulin by acacia gum in a fibre blend. Both blends were well fermented and the presence of acacia gum modified the intestinal fermentation of the blend from a boosted fermentation into a gradual one in the complete colon. Confirmation of the gradual fermentation was obtained by analysis of the pH profile, measurement of the residual acacia gum fractions in the colon and by the increased expression of specific catabolic enzymes. Both blends increased the total amount of short chain fatty acids (SCFAs; +42 mmol/L), propionate (+26 mmol/L) and butyrate (+9 mmol/L) and showed bifidogenic properties. Metagenomic Illumina sequencing confirmed that the blends exerted a diverse modulating activity in the different areas of the colon. Long-term repeated administration of the prebiotic blends is needed to reach gradual changes in the gut microbial community structure and activity. The partial substitution of FOS and inulin by acacia gum slowed the speed of the fermentation of the blend. In humans, this may translate into benefits for gut health, allowing for incorporation of higher amounts of fibre into the diet.